The Effect OF CAR, NPF, and BOPO on ROA in Islamic Commercial Banks for the 2017-2024 - Ulvia Firdayanti; Candra Febrilyantri (Falahiya Journal of Islamic Banking and Finance, 2026)
Introduction: this research is motivated by the fluctuation of probability (ROA) in Islamic Commercial Banks in Indonesia, which is influenced by capital conditions, financing quality, and operational efficiency. ROA stability serves as a crucial indicator in assessing bank performance; thus, empirical analysis is required to determine the effect of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Operating Expenses to Operating Income (OEOI/BOPO). Research Methods: this study employs a quantitative of five Islamic commercial banks (BUS) during period of 2017-2024. The analysis technique used is panel data regression via Eviews9 software, involving model section stages through the Chow test and Hausman Test. Based on the test result, the Random Effect Model (REM) was selected as the best model Results and Conclusion: indicate that partially, CAR does not have a significant effect on ROA, meanwhile NPF and OEOI/BOPO has a significant negative effect on ROA. Simultaneously, CAR, NPF, and OEOI/BOPO significantly affect ROA with a coefficient of determination (R2) of 0,542, indicating that 54,2% of the variation in ROA can be explained by these three variables, while the remaining 45,8% is influenced by factor outside this research.